The efficacy and safety of fractional erbium yag laser combined with topical amniotic membrane stem cell (AMSC) metabolite product for facial rejuvenation: A controlled, split-face study - Ni Putu Susari Widianingsih; Trisniartami Setyaningrum; Cita Rosita S. Prakoeswa (PAGEPress Publications, 2019)
Skin aging is a complex biological process, and it growing fast in number. Fractionated laser has been considered as the gold standard for skin rejuvenation. Stem cell-based therapy also becoming a promising new approach for treating this condition. To investigate the effect of fractional erbium laser and topical amniotic membrane stem cell (AMSC)-metabolite product (MP) on skin aging. A total of 9 female participants, were included in controlled split-face study. The participant's face was randomly allocated to AMSC-MP or saline, immediately after fractional laser procedure. All participants received 3 sessions of treatment with 4-weeks intervals. An evaluation was done using pre- and post- treatment photographs and skin analyzer, Janus. Laser-assisted transdermal delivery drug using topical AMSC-MP give a better improvement on skin pore and spot UV compared with the control group. The wrinkle and skin tone showed different results maybe because of multifactorial factors influence. No serious adverse events were found. This study suggest that fractional erbium YAG laser treatment combined with topical AMSC-MP is effective and safe for facial rejuvenation in Asian patients.